2013
DOI: 10.1534/genetics.113.157370
|View full text |Cite
|
Sign up to set email alerts
|

Resection Activity of the Sgs1 Helicase Alters the Affinity of DNA Ends for Homologous Recombination Proteins inSaccharomyces cerevisiae

Abstract: The RecQ helicase family is critical during DNA damage repair, and mutations in these proteins are associated with Bloom, Werner, or Rothmund-Thompson syndromes in humans, leading to cancer predisposition and/or premature aging. In the budding yeast Saccharomyces cerevisiae, mutations in the RecQ homolog, SGS1, phenocopy many of the defects observed in the human syndromes. One challenge to studying RecQ helicases is that their disruption leads to a pleiotropic phenotype. Using yeast, we show that the separatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 48 publications
5
21
0
Order By: Relevance
“…NATURE COMMUNICATIONS | DOI: 10.1038/ncomms6004 ARTICLE that sgs1D664D allele is proficient in the resolution of telomere recombination intermediates but defective in resection 57 , these results indicate that Sgs1 also contributes to resection of eroded telomeres. Noteworthy, although it has an opposite effect on the kinetics of senescence, the sgs1D664D allele impaired the formation of type II survivors as did the full deletion of the gene 33 ( Fig.…”
Section: Nature Communications | Doimentioning
confidence: 79%
See 1 more Smart Citation
“…NATURE COMMUNICATIONS | DOI: 10.1038/ncomms6004 ARTICLE that sgs1D664D allele is proficient in the resolution of telomere recombination intermediates but defective in resection 57 , these results indicate that Sgs1 also contributes to resection of eroded telomeres. Noteworthy, although it has an opposite effect on the kinetics of senescence, the sgs1D664D allele impaired the formation of type II survivors as did the full deletion of the gene 33 ( Fig.…”
Section: Nature Communications | Doimentioning
confidence: 79%
“…To address this possibility, we used the sgs1D664D separation of functions allele 55 . This allele has a defect in the processivity of resection at DSBs 56,57 . In agreement with previous report 33 , we found that full deletion of SGS1 accelerated the loss of viability of est2D cells, although the defect was less pronounced in our strain background (Fig.…”
Section: Nature Communications | Doimentioning
confidence: 99%
“…SAE2 is required for activating Mre11 endonuclease activity (Cannavo and Cejka 2014). Given the strong genetic interaction with sae2D, we hypothesized that Thr675 on Xrs2 may function in a parallel pathway of activating Mre11 endonuclease activity, which is essential for timely removal of the MRX complex from DSB ends, and the retention of MRX results in prolonged checkpoint activation and growth defects (Clerici et al 2006;Bernstein et al 2013;Chen et al 2015). Our genetic studies showed that tel1D and mec1D checkpoint mutants suppressed the severe sensitivity of an xrs2 S349A, T675A sae2D strain to MMS ( Figure 5B), consistent with the idea that prolonged checkpoint activation is responsible for the severe MMS-sensitivity phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The Mre11 complex plays a parallel role with Exonuclease 1 (Exo1) in producing long-range ssDNA tails (Bernstein et al 2013;Cannavo and Cejka 2014). The genetic interaction of xrs2 S349A, T675A with exo1D raises the possibility that The genetic interactions with tof1 S379A, S626A and xrs2 S349A, T675A were selected from the manually curated genetic interactions with tof1D and xrs2D in the Saccharomyces Genome Database (http://www.yeastgenome.org/).…”
Section: Selection Of Biologically Important Phosphorylation Sites Fomentioning
confidence: 99%
See 1 more Smart Citation